2007
DOI: 10.1063/1.2711204
|View full text |Cite
|
Sign up to set email alerts
|

Local integrals and their globally connected invariant structure in phase space giving rise to a promoting mode of chemical reaction

Abstract: We develop a method to extract local integrals, that is, integrals defined locally in the linear regime of an arbitrary point in phase space. The individual integral represents a vibrational mode. We also propose an index that quantifies the extent of connection between neighboring local integrals. Those pieces that are smoothly connected over a wide range represent a global structure of phase space. With a six-atomic Lennard-Jones cluster, we show that it is possible to identify which vibrational mode in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We demonstrated our method in the two systems and showed that the actions constructed by our method have larger validity ranges than those by the conventional ones and our previous method proposed in [1,2]. Previously, Padé approximations have also been used to improve validity ranges of LCPT [81][82][83][84][85][86]. Empirically, these approximations work well and poles of the Padé approximation tend to clump together in the regions where chaotic motion is observed, such as separatrices or other chaotic regions [81,84].…”
Section: Conclusion and Discussionmentioning
confidence: 81%
“…We demonstrated our method in the two systems and showed that the actions constructed by our method have larger validity ranges than those by the conventional ones and our previous method proposed in [1,2]. Previously, Padé approximations have also been used to improve validity ranges of LCPT [81][82][83][84][85][86]. Empirically, these approximations work well and poles of the Padé approximation tend to clump together in the regions where chaotic motion is observed, such as separatrices or other chaotic regions [81,84].…”
Section: Conclusion and Discussionmentioning
confidence: 81%